Perbedaan Kadar Zinc Rambut dan Asupan Makan pada Balita Stunting dan Non-Stunting di Puskesmas Wilangan Kabupaten Nganjuk - Ririn Kristiani; Luki Mundiastuti; Trias Mahmudiono (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2019)
Background: Chronic nutritional problems that occur in the world and Indonesia is stunted. Deficiency of nutrient intake is one of the direct causes of stunted. Zinc deficiency can cause growth failure, decreased appetite and failure of motor development. Zinc hair concentration is more appropriate to describe zinc status in the past and easier implementation, the handling is simpler and concentration is more sensitive.Objectives: Analyzing differences of zinc hair concentration and food intake (energy , protein, zinc and iron) on stunted and non-stunted at Wilangan Health Center.Methods: This was analytic observational with cross sectional study. Total of samples was 23 stunted toddlers and 23 non-stunted toddlers. Samples were taken randomly. Body height data using mikrotoice, zinc hair concentration with Atomic Absorption Spectrophotometry, food intake with 3x24 hours food recall and questionnaire interviews. Data were analyzed by chi-square, independent t-test and logistic regression.Results: There was differences in hair zinc levels (p = 0.039), energy intake (p = <0.001), protein intake (p = <0.001), zinc intake (p = <0.001) and iron intake (p = 0.003).Conclusions: There was difference betwen low zinc hair levels, energy, protein, zinc and iron intake in toodlers stunted and non-stunted. Hair zinc levels, energy, protein, zinc and iron intake in toodlers stunted was lower than non-stunted at Wilangan Health Health Center.ABSTRAKLatar Belakang: Permasalahan gizi kronis yang terjadi di dunia dan Indonesia salah satunya adalah stunting. Kurangnya asupan zat gizi merupakan salah satu penyebab langsung terjadinya stunting. Defisiensi zinc dapat menyebabkan kegagalan pertumbuhan, penurunan nafsu makan dan kegagalan perkembangan motorik. Kadar zinc rambut lebih tepat untuk menggambarkan status zinc pada masa lampau dan pelaksanaan yang lebih mudah, penanganan lebih sederhana dan konsentrasinya lebih peka.Tujuan: Menganalisis perbedaan kadar zinc rambut dan asupan makan (energi, protein, zinc dan zat besi) pada balita stunting dan non-stunting di Puskesmas Wilangan.Metode: Rancangan yang digunakan yaitu observasional analitik dengan case control design. Jumlah sampel 23 balita stunting dan 23 balita non-stunting. Pengambilan sampel dilakukan secara acak. Data tinggi badan menggunakan mikrotoice, kadar zinc rambut dengan metode Spektrofotometri Serapan Atom, asupan makan dengan food recall 3x24 jam dan wawancara kuesioner. Data dianalisis dengan uji chi-square (kadar zinc rambut), dan t-test dependen (asupan makan).Hasil: Terdapat perbedaan kadar zinc rambut (p=0,039), asupan energi (p=<0,001), asupan protein (p=<0,001), asupan zinc (p=<0,001) dan asupan zat besi (p=0,003) pada balita stunting dan non-stunting.Kesimpulan: Terdapat perbedaan kadar zinc rambut, asupan energi, protein, zinc dan zat besi balita stunting dan non-stunting. Kadar zinc rambut, asupan energi, protein, zinc dan zat besi pada balita stunting lebih rendah dibandingkan balita non-stunting di wilayah Puskesmas Wilangan.